PENGARUH PEMBELAJARAN WORD WALL UNTUK MENINGKATKAN PEMAHAMAN PERKALIAN PADA SISWA KELAS RENDAH - Azahra, Najla Imey (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2025)
This study aims to examine the effect of using Word Wall media in improving multiplication understanding in lower grade students at SDN Karang Mekar Mandiri 1. The method used is quantitative with pretest and posttest design, as well as filling out student response questionnaires. The results of the analysis showed a significant increase in student scores after learning using Word Wall (p <0.05), as well as very positive student responses to this media. Media validation by ICT experts obtained a score of 87.5%, indicating that the media is feasible to use. Observations during the learning process showed a high level of active student participation. Overall, the study concluded that Word Wall media is effective and feasible to use to improve understanding of multiplication concepts and active student participation in elementary mathematics learning.